Harmonisasi Moderasi Beragama Muslim Perbatasan Aceh - Sumatera dan Tradisi Lokal - Subakat, Rahayu; Salam, Mahdi W; Fahrurriza, Fahrurriza; Munandar, Imam (IAIN Ponorogo, 2025)
This study aims to explain the existence of border community harmony in multicultural and religious social interactions. The border areas of Aceh and North Sumatra in this mountainous community are known to have ethnic and cultural diversity that influences the social dynamics and religiosity of the local community. This study uses a qualitative approach through participatory observation techniques, in-depth interviews, and document analysis. The study results indicate that socio-religious harmony in this area is realized through religious moderation values, which are indicated by tolerance of religious communities, positive dialogue between religious communities, and respect for local traditions. Religious figures, community leaders, and educational institutions are important in educating and advocating for an understanding of religious harmony.